Recent Advances in Aqueous Zinc‐ion Hybrid Capacitors: A Minireview - Yanyan Shao; Dr. Fei Shen; Prof. Yuanlong Shao (ChemElectroChem)
Abstract The tremendous demand for wearable electronic systems drives increasing efforts devoted to research on portable electrochemical energy storage devices. Thanks to the environmental benignity, highly intrinsic safety and low cost, zinc‐ion based charge storage systems have attracted extensive attention recently. Zinc‐ion hybrid capacitors (ZHCs) stand for the electrochemical energy storage system with a capacitive electrode as cathode and a zinc metal as the anode. In this minireview, we summarize the history of aqueous ZHCs and present a comprehensive overview of the recent progress in the structure design, charge storage mechanisms and electrochemical properties of the cathode, anode, as well as the electrolytes and their effects on the electrochemical performance of final ZHCs. In the end, the current challenges and our perspectives on the future trends of this field are also briefly anticipated. The pertinent insights into the challenges on the electrodes and electrolyte systems could also shed some lights on other aqueous electrolyte based electrochemical charge storage systems.